Where We Live and Where We Leave: An Exploratory Study about Online Community Participation and Consumption Cycle in Taiwan - SHEN, CHIA-YU (2010)
In the postmodern age, each unique individual attends in different tribes and shares common interests within the tribes. With the development of ICTs, the emergence of online community is considered to be the new social phenomenon worth researching. Although there are a wide range of studies looking at this area for various purposes in different focuses, it is argued that there is little to be known about (a) how individuals enter and exit online communities across their lifetime and (b) how consumers and communities consume and are consumed by each other. In fact, there is rather less investigation on the chosen context: the net generation in Taiwan. In respond, this study has been carried out with the focus on the online community engagement of the Taiwanese net generation. To this length, this dissertation attempts to investigate how individuals enter, engage in, utilise, contribute on, and finally exit online communities for different reasons. From the integrative interpretive and postmodern perspective, the research has conducted an exploratory qualitative research with 9 online synchronous interviews. Both netnographic and narrative analytical techniques have been adopted to analyse the collected data. After discussing the findings about the participating trends, diverse narratives, online social links, participation patterns, engagement level and reasons to enter/exit online communities, this dissertation has proposed an integrative model of participation and consumption model to illustrate how individuals and online communities change and influence each other in a dynamic way. From this model, this research gives rise to the theoretical and managerial implications with further contention about the recommendations for future research.